Genotype × environment interaction studies in summer groundnut (Arachis hypogaea L.): Genotype × environment interaction studies in summer groundnut (Arachis hypogaea L.) - N D SARODE; V L AMOLIC (Journal of Oilseeds Research, 2020)
A field experiment was carried out at All India Co-ordinated Research Project on Groundnut, Cotton Project, MPKV, Rahuri during summer 2016, with ten groundnut genotypes. The present study indicated that sowing of groundnut varieties on the date E2 (15th February) was most favorable for expression of yield and yield contributing traits. It is concluded that groundnut genotypes Phule Unnati, SB-XI, Phule-6021, Phule Bharati, TAG-24 and JL- 501 from average yield group were observed to be stable for yield and yield contributing characters.